Konstribusi Akumulasi Silikat, Nitrogen dan Aluminium terhadap Ketenggangan Aluminium dan Ketahanan terhadap Penyakit Blas pada Padi Gogo - , Bakhtiar; Bambang Sapta Purwoko; , Trikoesoemaningtyas; Iswari Saraswati Dewi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Aluminum (Al) toxicity and blast disease are the most important yield-limiting factors for upland rice production in acid soils. The objective of this experiment was to examine the contribution of accumulation of Silicate (Si), Nitrogen (N) and Al in plant tissue on Al tolerance and blast disease resistance in upland rice. The experiment was arranged in a split-split plot design with 2 replications. Main plots were randomly assigned to blast treatment (control and inoculation to blast fungi). Subplots were assigned to control box (lime 1.5 AlEC) and another acid soils (no lime) box and sub-subplots were assigned to the tested genotypes. The result of the experiment showed that leaf blast disease resistance in rice cannot be solely explained by Si or N content in shoot tissue. The resistant to leaf blast disease might be attributed by high ratio Si/N weight in shoot. Al tolerance was ascribed by low reduction in root growth, high shoot dry weight, high Si content in shoot, and as well as high of Si/Al ratio in root. Key words: Al-tolerance, blast disease, upland rice, Si/Al ratio